The Use of Past Tenses Referring to The Time Prior to The Past in Narrative Texts - Dočekalová, Andrea (Univerzita Pardubice, 2010)
This thesis examines the use of past tenses in narrative texts called urban legends. The aim of the paper is to find out differences in expressing the time prior to the past within the defined stages of the analysed tales. Theoretical part provides a description of semantic category of time and morphological category of tense. Further the system of English tenses is characterized and the possible expressions of the more remote time follow. This part also provides a description of urban legends as a genre. The analysis deals with the found differences among the use of two tenses for expressing the time prior to the past within the three basic stages of the narrative.Práce se zabývá výzkumem použití minulých časů ve vyprávění zvaném městské legendy. Cílem této práce je najít rozdíly ve vyjadřování předminulosti v rámci tří částí, na které jsou analyzované příběhy rozděleny. Teoretická část poskytuje popis sémantické a morfologické kategorie času. Dále je charakterizován systém anglických časů a následuje určení typů předminulostí. Tato část také popisuje městské legendy jako žánr. Analýza se zabývá vyskytujícími se rozdíly v užití dvou časů pro odkazování na předminulost v rámci tří základních částí struktury vyprávění.
Užití minulých časů pro odkazování na předminulost ve vyprávění
Keywords: předminulost; minulý čas; předminulý čas; vyprávění; tense; aspect; time prior to the past; past tense; past perfect tense; narrative; time